Intraoperative Detection of Efferent Lymphatic Vessels Emerging from Lymph Node during Lymphatic Microsurgery - Akita, Shinsuke; Yamaji, Yoshihisa; Kuriyama, Motone; Tokumoto, Hideki; Ishigaki, Tatsuya; Tezuka, Takafumi; Ogata, Hideyuki; Kubota, Yoshitaka; Mitsukawa, Nobuyuki (Journal of Reconstructive Microsurgery, 2019)
Background Although the usefulness of efferent lymphaticovenular anastomosis (ELVA) in lymphatic microsurgery has been reported, the optimal method to distinguish efferent from afferent lymphatics is not yet established. We propose a novel technique to detect efferent lymphatics appropriate for anastomosis.Methods In total, 62 groin lymph nodes (LNs) of 46 limbs were divided into four groups based on the findings of indocyanine green lymphography: n = 15 in normal, 15 in dermal backflow stage 0, 18 in stage I, and 14 in stage II groups. The target LN and afferent lymphatic connecting it were preoperatively detected using ultrasonography. Intraoperatively, 0.05 mL patent blue dye was slowly manually injected from the afferent lymphatic; the lymphatic(s) subsequently stained was diagnosed as the efferent lymphatic(s) emerging from the node. The success rates of efferent lymphatic detection, sizes of LN, and diameter of efferent lymphatics were compared among the groups.Results Both LN size and diameter of efferent lymphatic were significantly larger in the stage 0 and I groups than the other groups (p < 0.01). Efferent lymphatic could be stained in 13, 13, 18, and 9 LNs in the normal and stage 0, I, and II groups, respectively. A significant difference was observed between the stage I and II groups regarding the success rate of efferent lymphatic detection (p = 0.04).Conclusion Efferent lymphatics could be detected using patent blue dye in 85.5% of the cases. The patients in early-stage lymphostasis might be the most appropriate candidates for ELVA.
Keywords: lymphedema; efferent lymphatic; lymphaticovenular anastomosis